Exploring the reticulo-ruminal motility pattern in goats through medical barium meal imaging technology - Song, Yang; Lan, Xinyi; Liu, Lei; Wan, Fachun; Shen, Weijun; Wang, Zuo (Frontiers in Veterinary Science, 2024)
The motility pattern of the reticulo-rumen is a key factor affecting feed intake, rumen digesta residence time, and rumen fermentation. However, it is difficult to study reticulo-ruminal motility using general methods owing to the complexity of the reticulo-ruminal structure. Thus, we aimed to develop a technique to demonstrate the reticulo-ruminal motility pattern in static goats. Six Xiangdong black goats (half bucks and half does, body weight 29.5±1.0 kg) were used as model specimens.Reticulo-ruminal motility videos were obtained using medical barium meal imaging technology. Videos were then analyzed using image annotation and the centroid method. The results showed that reticulo-ruminal motility was divided into primary (stages i, ii, iii, and iv) and secondary contraction, and the movements of ruminal digesta depended on reticulo-ruminal motility. Our results indicated common motility between the ruminal dorsal sac and ruminal dorsal blind sac. We observed that stages i (3.92 vs 3.21 s )(P<0.01), ii (4.81 vs 4.23 s)(P<0.01), and iii (5.65 vs 5.15 s)(P<0.05); interval (53.79 vs 50.95 s); secondary contraction time (10.5 vs 10 s); and were longer, whereas stage iv appeared to be shorter in the bucks than in the does (7.83 vs 14.67 s)(P<0.01). The feasibility of using barium meal imaging technology for assessing reticulo-ruminal and digesta motility was verified in our study. We determined the duration of each stage of reticulo-ruminal motility and collected data on the duration and interval of each stage of ruminal motility in goats. This research provides new insights for the study of gastrointestinal motility and lays a solid foundation for the study of artificial rumen.